Spiritual Communication for Disaster Mitigation in the Gunung Padang Area - West Java - J.A Wempi; Muhamad Hidayat; Ananto Akbar (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
Cianjur, West Java, is one of the areas with a  high level of disaster threats according to the Indonesia Disaster Risk Index report in 2022. One of the disaster threats is the 100-kilometer long Cimandiri Fault in West Java which is the oldest fault, not to mention the danger of landslides. .  Gunung Padang  is a disaster-prone area,  making  Gunung Padang at risk of being affected by tectonic earthquakes because it is situated between earthquake generating lines divided into fault segments that cross 17 districts in Sukabumi, Cianjur and Bandung. Religious and cultural aspects often play an important role in disaster mitigation, especially in communities with strong religious and cultural values. This research aims to analyze spiritual-based disaster communication in the Gunung Padang area, West Java. This research used descriptive qualitative methods and collected data through semi-structured interviews. The data used for this research is primary data to be obtained directly from the first source or original source,  including community leaders and local government by using observation and interview techniques. Meanwhile, the secondary data is obtained  from other supporting documents. The results of this study show that the people of the Gunung Padang area traditionally uphold and maintain the wisdom and spiritual aspects of Lok which have an important role in conveying disaster mitigation messages. This study also highlights the importance of local beliefs, which shape the community's disaster awareness and influence their thoughts, attitudes, and behaviors. The religious aspect of local wisdom encourages harmony with nature and prevents its exploitation. Spiritual communication plays a significant role in the lives of the Gunung Padang community and is an essential aspect of disaster awareness, which is based on the integration of knowledge, skills, and local wisdom.